(untitled) (Journal of Pharmaceutical Negative Results, 2023)
As a major virus outbreak in the twenty-first century, the Coronavirus disease 2019 (COVID-19) pandemic has posed unprecedented risks to global mental health. Because of the severity of the virus, people were forced to isolate themselves and confine themselves to their homes. This was linked to people's inability to work, seek help from loved ones, and participate in their communities. Stressors that contribute to anxiety and depression include loneliness, fear of infection, suffering and death for oneself and loved ones, bereavement grief, and financial worries. As a result, covid 19 is a source of psychological distress. This paper investigates the impact of these stressors on all age groups in society, including today's youth, the elderly, and even health workers. Because Buddhism has a longstanding experience with medicine and preaches calmness and acceptance of fear, it is not surprising that Buddhist ideas come to the aid of those in need during times of crisis. However, it receives little attention. Thus, this paper focuses on theories such as mindfulness meditations, engaged Buddhism, and cultivating compassion, all of which can aid in increasing positive emotions and thus reducing stressors.